The effect of a proposed sports therapy program on improving psychological health among patients with type 2 diabetes - Difallah, Habiba (Journal of Human Sciences, 2021)
This study aims to know the effect of the suggested sport program on the improvement of the psychological side of the diabetics, type 2. The research is based on the experimental method. Indeed, the sample of the study comprises 20 patients at the wilaya of M'sila, all of them were diabetic type2 which we divided into two groups, the first: the experimental group composed of (10) (Individuals) which are submitted to the suggested sport program and the second: the controlling group composed of (10) (individuals). Also, the members of this group did not have any training on the suggested sport program in the study.  The study tools were the standards of the psychological health (which was prepared by the researcher) and the suggested sport program (prepared by the researcher).Indeed, the study led to the following results:                                                                   There are statistically significant differences between the pre- and post-measurement of the effect of the proposed therapeutic sports program in improving the psychological health of patients with type 2 diabetes, in favor of the post-measurement.